Pemasaran elektronik pada era modern - Putri, Dieva Rullyeza Chelsealia (Maliki Interdisciplinary Journal, 2025)
e-marketing or also known as internet marketing and electronic marketing, refers to the application of communication and internet technology in a company’s marketing system. The term internet marketing is often used to describe how the internet can be used together with traditional media to attract and serve customers. E-marketing includes a variety of online marketing activities, such as through websites, digital advertising, email or mobile devices. In essence, e-marketing aims to bring companies closer to customers, understand their needs in more depth, and maintain continuous communication. This interactive and dynamic dialogue is at the heart of an effective marketing strategy. This writing was written to understand the development of electronic marketing, electronic marketing strategies to increase online sales amidst intense market competition, the application of electronic marketing in the current digital era, and the advantages and disadvantages of electronic marketing.